Middle Managers' Perspectives on Power Changes in Democratizing Organizational Transformations - Šimůnek, David; Mládková, Ludmila, 1963-; Kubátová, Jaroslava; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
Importance - This dissertation examines how middle managers experience power changes within transformations that shift organizational design to more democratized structures. These changes redistribute rights and responsibilities and shift organizations into flatter, more democratic designs. Research gap – The current research is extensive but focuses mainly on systems and procedures, with little attention to how these changes affect middle managers and how they perceive them. Research question - How do middle managers perceive and respond to power changes during democratizing transformation in traditionally managed organizations? Objectives - This dissertation aims to better understand the power changes associated with organizational democratization through middle managers’ interpretations and responses and related consequences. Furthermore, the dissertation seeks to understand the nature of middle managers' resistance to or acceptance of the change and to identify opportunities for optimizing the transformation process. Methods - The dissertation is based on empirical research into middle managers' lived experiences within large, traditional, regulated companies, utilizing a qualitative phenomenological approach. The primary data collection method included in-depth semi-structured interviews with 18 middle management representatives who transitioned from traditional to more autonomous forms of organizing due to democratizing transformation. The interviews with respondents were conducted in several iterations during the ongoing organizational changes over a period of one and a half years in two major corporations. The data were analysed using Interpretative Phenomenological Analysis (IPA) with an idiographic approach (within-case then cross-case) and a double-hermeneutic stance. The Foucauldian concept of power framed interpretation.
Key findings – Middle managers repeatedly perceive diminished power, which can evoke feelings of powerlessness and resistance. Data also reveal several mechanisms through which middle managers acquire alternative forms of power and place in alternative hierarchies. The studied managers’ responses are characterized by distinct patterns and determined also by personal coping strategies, alternative career support options, and the degree of identification with the organization's vision or interpretation of the situation itself. Implications - Transformations that partially redistribute power away from middle managers also create opportunities for new forms of power, including those with positive impacts on these individuals. This allows organizations to proactively define the future middle manager positions in democratized systems and to mitigate resistance more effectively while leveraging other productive aspects of change.
Vedoucí práce: Ludmila Mládková
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: management a manažerská ekonomie [obor disert. práce]; disertace; dissertations